A systematic review and meta-analysis of the prevalence of tick-borne SFGR in China from 2000 to 2022. - Yanchao Hu; Ting Yin; Wei Ma; Jiangwei Qiu; Jiaxing Zhang; Qingan Wang (Public Library of Science (PLoS), 2024)
Background Ticks carry and transmit a wide range of pathogens (bacteria, viruses, and protozoa) that pose significant threats to human and animal health worldwide. Only few meta-analyses have been conducted on the distribution of ticks and tick-borne spotted fever group rickettsia (SFGR). Therefore, this study aims to examine the tick species and SFGR positivity in China in order to provide support for further research and improvements in the prevention and control of tick-borne diseases. Methodology This systematic review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Relevant Chinese and English studies were retrieved from PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), VIP database, Chinese Biomedical literature database (CBM) and Wanfang database from inception to January 9, 2023. Pooled SFGR positive rate was meta-analyzed using a random effects model and heterogeneity was assessed by the I2 index. Publication bias was also evaluated by funnel plot and Egger's test. The meta-analysis was performed on R studio 4.0.4. Principal findings Meta-analysis of 57 studies published between 2000 and 2022 involving 39,380 ticks revealed a pooled SFGR positive rate of 21.4% (Q = 6423.74, I2 = 99%, Q-p<0.001, 95% CI: 15.0-29.6). Most studies of tick-borne SFGR infection rate were conducted in forest areas and developed animal husbandry areas in the northern region. There were slightly more tick species in the southern region, but the differences in tick species (Feeding tick 31.5%, 95%CI: 15.7-53.2, Questing tick 11.5%, 95%CI: 4.4-26.7, Q = 3.29, Q-p = 0.19) between areas (Northern area 20.4%, 95%CI: 14.1-28.7, Southern area 25.5%, 95%CI: 15.0-29.6, Q = 0.21, Q-p = 0.64) were not statistically significant. The most common tick species were Dermacentor silvarum (13%), Ixodes persulcatus (11%) and Haemaphysalis Iongicornis (10%), and the most prevalent SFGR species were Rickettsia raoultii (20%), Rickettsia heilongjiangiensis (11%), and some uncultured species (18%). Conclusions This study examined the distribution of tick-borne SFGR in China. Our findings revealed that the main tick species were D. silvarum, I. persulcatus and H. iongicornis, and the common SFGR species were R. raoultii, R. heilongjiangiensis, and some uncultured species. Further studies are warranted to identify the potential vectors of SFGR and to better understand the epidemiology and pathogenesis of tick-borne diseases in China.